Forsythiaside prevents β-amyloid-induced hippocampal slice injury by upregulating 2-arachidonoylglycerol via cannabinoid receptor 1-dependent NF-κB pathway. (May 2019) - Chen, Liqing; Yan, Yan; Chen, Tinggui; Zhang, Liwei; Gao, Xiaoxia; Du, Chenhui; Du, Huizhi
Abstract: In the study, the neuroprotectivities of forsythiaside, a main constituent of Forsythia suspensa (Thunb.) Vahl ( F. suspensa, Lianqiao in Chinese), were investigated in the hippocampal slices. Forsythiaside suppressed the overexpression of cyclooxygenase-2 (COX-2) and monoacylglycerol lipase (MAGL) proteins induced by β-amyloid (Aβ25-35 ) to upregulate the levels of 2-arachidonoylglycerol (2-AG), an endogenous endocannabinoids. Then the inhibition of forsythiaside on COX-2 was deeply studied by the molecular docking. Forsythiaside prevented neuroinflammation and apoptosis from Aβ25-35 insults, and this action appeared to be mediated via cannabinoid receptor 1 (CB1R)-dependent nuclear factor-κB (NF-κB) signaling pathways. More importantly, forsythiaside functionally improved Aβ25-35 -induced learning and memory deficits, which was indicated by long term potentiation (LTP). Taken together, forsythiaside may have therapeutic potential for Alzheimer's diseases (AD) by increasing the levels of 2-AG. Highlights: Forsythiaside inhibits COX-2 and MAGL over-expression induced by Aβ to up-regulate 2-AG. Forsythiaside prevents inflammation and apoptosis from Aβ via CB1R-dependent NF-κB pathway. Forsythiaside functionally improves Aβ-caused LTP deficits.